Applications and Considerations of GToTree: A User-Friendly Workflow for Phylogenomics. (July 2019) - Lee, Michael D
Phylogenomics is the practice of attempting to infer evolutionary relationships at a genome-level. This is becoming a standard step in the characterization of newly recovered genomes and to direct/constrain further research; yet the process from start to finish of building a de novo phylogenomic tree that is specific to the organisms of interest can still be computationally intractable for many biologists. GToTree is a recently published user-friendly workflow for phylogenomics intended to give more researchers the capability to generate phylogenomic trees to help guide their work. This commentary describes two common applications where GToTree can be helpful and then discusses some things to consider when using the program.